Health and nutritional status of 'target population' in Kachua thana, Bangladesh: baseline survey 1999 - Hyder, S.M. Ziauddin; Roy, Rita Das; JalaI, Chowdhury SB; Yusuf, Harun KM (BRAC Research and Evaluation Division (RED), 2019)
The state of nutrition in Bangladesh is precariously poor. The diet, being heavily deficient in calories and seriously imbalanced, leads to the obvious consequences of widespread protein-energy and micronutrient malnutrition among infants, children and women. This is a great loss of human resources potential for productivity and much of ·the low per capita gross domestic product (GOP) and low human development index (HOI) of the country (0.336) is attributable to this scourge of malnutrition. The overall health situation of the Bangladeshi population is also far below any acceptabie standard. This is particularly true for women and children with worst possible health statistics in terms of both morbidity and mortality. For example, the maternal mortality rate has been over 600 per 100,000 live births for many years. This has now improved slightly to about 470 per 100,000 live births. The latter figure is still one of the highest in the world. Similarly, 1 in 10 infant in Bangladesh does not live up to his/her first birthday; the infant mortality rate is around 80 per 1000 live births. The above circumstances had led the Institute for Integrated Rural Development (IIRD) to find out innovative and appropriate programs to overcome the deplorable health, nutrition and basic education scenario of the people of some selected areas in Bangladesh. The proposed project titled "Shadaron Shikha 0 Prathomic Shastho Sheba Prokolpo (SSP SSP)" has been formulated on the basis of that realisation. The Kachua Thana under Chandpur District is one such area where such a project has been taken up. On request from IIRD, the Research and Evaluation Division (RED) of BRAC undertook a baseline survey among the target households of the project area under Kachua thana of Chand pur District.